Efficacy of Soil Conditioners and Nitrogen Under Saline-Sodic Irrigation on Sugarbeet (Beta Vulgaris L). II. Physicochemical Properties of The Soil - Totawat, K L; Singh, R M (Annals of Arid Zone, 2016)
Cultivation of sugarbeet on light textured soil for two consecutive winter seasons had earlier resulted in an overall increase in bulk density and decrease in total air space, hydraulic conductivity, water holding capacity, aggregate's mean weight diameter and organic carbon content of the soil. Incorporation of soil conditioners and nitrogen to the soil substantially protected the soil from the adverse effect of sugarbeet cultivation.